2019
DOI: 10.3389/fendo.2019.00561
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Vulvovaginal Atrophy (VVA)/Genitourinary Syndrome of Menopause (GSM) for Healthy Aging in Women

Abstract: Vaginal health is an essential component of active and healthy aging in women at midlife and beyond. As a consequence of hormonal deprivation and senescence, the anatomy and function of urogenital tissues are significantly affected and vulvovaginal atrophy (VVA) may occur. In a high proportion of postmenopausal women, progressive and chronic VVA symptoms have a strong impact on sexual function and quality of life. The new definition of genitourinary syndrome of menopause (GSM) comprises genital symptoms (dryne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 127 publications
(141 reference statements)
0
65
0
6
Order By: Relevance
“…Assessing health-related quality of life has been the subject of countless studies and publications, mainly starting in the first decade of the 21st century. At a time when technology is overemphasized in Medicine, sustaining and enhancing QoL involves making healthcare more focused on people, and various studies have shown that the QoL of postmenopausal women with LUTS is seriously compromised in several contexts, such as at work, in relationships and their social lives [4] [6] [7]. The literature also suggests that vaginal estriol improves vaginal trophism and reduces LUTS, leading to a positive effect on QoL [9] [17] [18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessing health-related quality of life has been the subject of countless studies and publications, mainly starting in the first decade of the 21st century. At a time when technology is overemphasized in Medicine, sustaining and enhancing QoL involves making healthcare more focused on people, and various studies have shown that the QoL of postmenopausal women with LUTS is seriously compromised in several contexts, such as at work, in relationships and their social lives [4] [6] [7]. The literature also suggests that vaginal estriol improves vaginal trophism and reduces LUTS, leading to a positive effect on QoL [9] [17] [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some women may feel uncomfortable discussing sexual matters, but this becomes necessary due to the high frequency of symptoms related to sex life, affecting nearly 50% of women in the postmenopausal period, negatively affecting their self-esteem and intimacy with their partner, and lowering their QoL [3] [27]. Studies have shown that women who use vaginal estriol have positive effects on their sexual function and QoL [4] [28] [29]. Despite its importance, we decided not to perform a statistical analysis in this domain due to a lack of consistency in the responses we obtained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations